THE INFLUENCE OF PERCEPTIONS OF THE TEACHER PROFESSION AND PARENTS' INCOME ON THE INTEREST IN PARTICIPATING IN TEACHR PROFESSIONAL EDUCATION (PPG) IS MEDIATED BY THE MOTIVATION TO BECOME A TEACHER - Rahma, Meita Anisya; Karyaningsih, RR Ponco Dewi; Febriantina, Susan (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
This study aims to determine the influence of perceptions of the teacher profession, parents' income, motivation to become a teacher, and interest in participating in teacher professional education. The study was conducted for 10 (ten) months starting from March 2021 to December 2021. Quantitative research methods with the type of research, namely explanatory. The sample used in this research amounted to 150 respondents of educational students of the Faculty of Economics, State University of Jakarta. Data on the variables of perception of the teacher profession, parental income, motivation to become a teacher and interest in participating in teacher professional education are primary data using a Likert scale. The data collection technique uses a proportional random technique. The results showed that the perception of the teacher profession has an influence on the interest in following (PPG), parental income has no influence on the interest in following (PPG), motivation being a teacher has an influence on the interest in following (PPG), the perception of the teacher profession has an influence on the motivation to become a teacher, the income of parents has no influence on the motivation to become a teacher, the perception of the teacher profession has an influence on the interest in following (PPG) through motivation to be a teacher as a mediation variable. parents' income has no influence on the interest in participating in PPGr through the motivation to become a teacher as a mediation variable.